Caribou, river and ocean: Harvaqtuurmiut landscape organization and orientation - Keith, Darren (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2004)
AbstractThe Harvaqtuurmiut were an Inuit society whose territory was Harvaqtuuq—the lower Kazan River—between the outlet of Hikuligjuaq (Yathkyed Lake) and the river’s mouth at Qamani’tuaq (Baker Lake). The Harvaqtuurmiut lived a completely inland existence and their subsistence revolved largely around the migration of caribou. In Harvaqtuurmiut perception, the landscape was organized and given orientation by three important influences: the migration of caribou; the flow of the river; and the relative location of the ocean. The organizing and orienting effects of these three influences are demonstrated through an analysis of Harvaqtuurmiut place names. Concepts related to the flow of the river and the relative location of the ocean were imbedded in the Inuktitut language at the time of Inuit migration to Harvaqtuuq in the mid-19th century. The environmental force of the caribou migration became very influential in Harvaqtuurmiut perception of landscape organization and orientation only after they had adapted to subsistence inland.